RELATIONSHIP BETWEEN DRINKING WATER HABITS AND WORK CLIMATE PERCEPTIONS WITH DEHYDRATION INCIDENCE IN SHIPPING COMPANIES’ WORKERS - Isas Awwalina; Shintia Yunita Arini; Tri Martiana; Putri Ayuni Alayyannur; Endang Dwiyanti (Universitas Airlangga, 2022)
Introduction: Workers in the maintenance and repair division's shipping division work in outdoor physical environments, which get hot temperatures from the environment. They cause excessive sweating while working and can cause dehydration if not drinking enough water. Methods: This study aimed to analyze the relationship between drinking habits and work climate perception with dehydration status in shipping companies' workers. The research method was analytic observational, with a cross-sectional design in 2019 in one of the shipping companies with a sample size of 49 workers who were selected using simple random sampling from 55 worker populations. The independent variables included respondent characteristics, drinking water consumption habits, and work climate perceptions, while the dependent variable was dehydration status. Dehydration status among workers was measured base on the specific gravity of urine measured in the laboratory, and the working climate was measured using a heat stress monitor. Result: The results showed that 85.71% of workers had minimum dehydration status, and 14.29% had significant dehydration. Then, there was a meaningful relationship between drinking water habits and dehydration status (r = -0.320 and p = 0.025). There was also a relationship between workers' work climate perceptions and dehydration status (r = -0.283 and p = 0.049). Conclusion: The relationship showed a weak negative meaning that the less habit of drinking water among workers, the higher the dehydration status of the workers. The more disturbed they perceive the working climate; the less dehydrated status of workers will be. So it can be ignored that there were drinking habits and the work climate perceptions with dehydrated status in shipping companies' workers. Keywords: dehydration status, drinking habits, work climate perceptions.